2015
DOI: 10.1016/j.jceh.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Liver Sinusoidal Non-Hodgkin's Lymphoma Presenting as Acute Liver Failure

Abstract: We describe a case of a middle-aged woman, who presented to us with fever, anorexia, abdominal distension from a massive hepatomegaly, low hemoglobin, and acute liver failure. A liver biopsy revealed B cell non-Hodgkin's lymphoma predominantly in the sinusoids with CD10, CD20, and Bcl-2 positive on immunohistochemistry. She initially responded well to chemotherapy but succumbed 6 months later to the recurrence of disease. Sinusoidal non-Hodgkin's lymphoma of the liver should be considered in the differential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Abnormal laboratory findings include elevated liver function aminotransferases, bilirubin, γ-glutamyl transferase, ALP and LDH. Approximately 70% of cases present with abnormal liver function enzymes, 30 to 80% with elevated LDH, 90% with elevated β2-microglobulin, and 80% with elevated ALP[ 17 - 20 ]. Mitarnun et al[ 20 ] reported that out of 100 patients with EBV associated H-PTCL, ALP was found elevated in 80%, while LDH was elevated in 65% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal laboratory findings include elevated liver function aminotransferases, bilirubin, γ-glutamyl transferase, ALP and LDH. Approximately 70% of cases present with abnormal liver function enzymes, 30 to 80% with elevated LDH, 90% with elevated β2-microglobulin, and 80% with elevated ALP[ 17 - 20 ]. Mitarnun et al[ 20 ] reported that out of 100 patients with EBV associated H-PTCL, ALP was found elevated in 80%, while LDH was elevated in 65% of cases.…”
Section: Discussionmentioning
confidence: 99%